Oto Bihalji-Merin and the Concept of the “Naïve” in the 1950s. Bridging Socialist Realism and Non-Figurative Art - Tanja Zimmermann (Acta Historiae Artis Slovenica, 2019)
Yugoslav writer, art critic and curator Oto Bihalji-Merin (1904–1993) lived in Berlin during the 1920s, where he joined the German Communist Party and published literary critique in the left-wing press. Born into a Jewish family, he moved to Czechoslovakia, France, Switzerland, and Spain after the rise of the Nazi regime. In this period, he established close contact with left-wing intellectuals from all over Europe. During the Second World War, he was imprisoned as a Yugoslav soldier by the Germans. After the war, he became the most important cultural theorist and administrator in Tito’s Yugoslavia. After Tito’s break with Stalin, he promoted the concept of naïve folk art as an authentic, primordial expression of proletarian and peasant creativity. His doctrine, destined to bridge the gap between socialist realism and Western non-figurative art, was inspired by Miroslav Krleža’s cultural theory of the Third Way and by the non-aligned movement.